2011
DOI: 10.1155/2011/968286
|View full text |Cite
|
Sign up to set email alerts
|

Independently Rotating Wheels with Induction Motors for High‐Speed Trains

Abstract: Railway vehicles with conventional wheelsets often experience problems of lateral instabilities or severe wear when running at high speed. The use of an independently rotating wheelset (IRW) can potentially eliminate the cause of wheelset hunting and reduce wheel wear as the mechanical feedback mechanism causing the problem is decoupled. This paper presents an investigation into the design of a novel induction motor configuration and controller for IRW in order to provide the stability required to satisfy the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…The investigated wheelset and bogie frame (see Fig. 1) on roller system can be defined via the following equations of motion, as a modification from [27] and [28] for two solid axle wheelsets and steering of leading wheelset as follows:…”
Section: Investigated Wheelset and Bogie Systemmentioning
confidence: 99%
“…The investigated wheelset and bogie frame (see Fig. 1) on roller system can be defined via the following equations of motion, as a modification from [27] and [28] for two solid axle wheelsets and steering of leading wheelset as follows:…”
Section: Investigated Wheelset and Bogie Systemmentioning
confidence: 99%
“…and Goodal, R. [42,43] Liang, B., Liu, X.Y. and Iwnicki, S. [44,45], Konowrocki, R. and Kalinowski, D. [46,47], Farhat, N. and Ward, C.P. [48,49], Chudzikiewicz, A.…”
Section: A Current State Of the Problemmentioning
confidence: 99%
“…Most researchers and engineers considered that the hunting motion was eliminated on the IRW in previous research, but the hunting phenomenon on the IRW has already been observed in some simulations or practical experiments conducted by different research groups. Liang and Iwnicki [17] built an IRW simulation model in Simulink and an IRW experiment system with a test rig. They found that lateral oscillation would occur at high speeds without an active motor control.…”
Section: Introductionmentioning
confidence: 99%